Ten-year outcome following surgical treatment of femoroacetabular impingement: does the evolution of surgical technique influence outcome?. (1st October 2022) - Grammatopoulos, George; Laboudie, Pierre; Fischman, Daniel; Ojaghi, Reza; Finless, Alexandra; Beaulé, Paul E.
Abstract : Aims: The primary aim of this study was to determine the ten-year outcome following surgical treatment for femoroacetabular impingement (FAI). We assessed whether the evolution of practice from open to arthroscopic techniques influenced outcomes and tested whether any patient, radiological, or surgical factors were associated with outcome. Methods: Prospectively collected data of a consecutive single-surgeon cohort, operated for FAI between January 2005 and January 2015, were retrospectively studied. The cohort comprised 393 hips (365 patients; 71% male (n = 278)), with a mean age of 34.5 years (SD 10.0). Over the study period, techniques evolved from open surgical dislocation (n = 94) to a combined arthroscopy-Hueter technique (HA + Hueter; n = 61) to a pure arthroscopic technique (HA; n = 238). Outcome measures of interest included modes of failures, complications, reoperation, and patient-reported outcome measures (PROMs). Demographic, radiological, and surgical factors were tested for possible association with outcome. Results: At a mean follow-up of 7.5 years (SD 2.5), there were 43 failures in 38 hips (9.7%), with 35 hips (8.9%) having one failure mode, one hip (0.25%) having two failure modes, and two hips (0.5%) having three failure modes. The five- and ten-year hip joint preservation rates were 94.1% (SD 1.2%; 95% confidence interval (CI) 91.8 to 96.4) and 90.4% (SD 1.7%; 95% CI 87.1 to 93.7), respectively. Inferior survivorship was detected in the surgical dislocation group. Age at surgery, Tönnis grade, cartilage damage, and absence of rim-trimming were associated with improved preservation rates. Only Tönnis grade was an independent predictor of hip preservation. All PROMs improved postoperatively. Factors associated with improvement in PROMs included higher lateral centre-edge and α angles, and lower retroversion index and BMI. Conclusion: FAI surgery provides lasting improvement in function and a joint preservation rate of 90.4% at ten years. The evolution of practice was not associated with inferior outcome. Since degree of arthritis is the primary predictor of outcome, improved awareness and screening may lead to prompt intervention and better outcomes. Cite this article: Bone Jt Open 2022;3(10):804–814.